A Commentary on Q. Curtius Rufus' Historiae Alexandri Magni : Books 3 and 4 - Atkinson, J E. (Classical Studies - Book Archive pre-2000., 1980)
Atkinson, J.E. A Commentary on Q. Curtius Rufus' Historiae Alexandri Magni. Books 3 and 4. 1980 Curtius Rufus' Historiae Alexandri is one of the major sources for the record of Alexan-der the Great as military commander, empire builder, administrator and political boss. This commentary covers the first two extant books, which include the battles of Issus and Gaugamela, the sieges of Tyre and Gaza, Alexander's invasion of Egypt and his visit to the oracle at Siwah. This is primarily an historical commentary, but also offers interrelated analyses of Curtius' literary style and sources. LSCP 4 (1980), 501 p. - 65.00 EURO, ISBN: 9070265613